Promoting multilingual practices in school and home environments - Szczepaniak-Kozak, Anna; Farrell, Angela; Ballweg, Sandra; Daase, Andrea; Wąsikiewicz-Firlej, Emilia; Masterson, Mary

HIEF: a holistic interpretability and explainability framework - Kucklick, Jan-Peter (Journal of Decision Systems)
Many applications are driven by Machine Learning (ML) today. While complex ML models lead to an accurate prediction, their inner decision-making is obfuscated. However, especially for high-stakes decisions, interpretability and explainability of the model are necessary. Therefore, we develop a holistic interpretability and explainability framework (HIEF) to objectively describe and evaluate an intelligent system’s explainable AI (XAI) capacities. This guides data scientists to create more transparent models. To evaluate our framework, we analyse 50 real estate appraisal papers to ensure the robustness of HIEF. Additionally, we identify six typical types of intelligent systems, so-called archetypes, which range from explanatory to predictive, and demonstrate how researchers can use the framework to identify blind-spot topics in their domain. Finally, regarding comprehensiveness, we used a random sample of six intelligent systems and conducted an applicability check to provide external validity.
Keywords: Explainable AI (XAI); machine learning; interpretability; real estate appraisal; framework; taxonomy

Sprachsensibles Arbeiten mit Hadithen im Islamischen Religionsunterricht - Kamcili-Yildiz, Naciye (Hadithdidaktik im Diskurs)

Was heißt religiöses gebildet? Konzepte religiöser Bildung von islamischen Religionspädagogen - Kamcili-Yildiz, Naciye; Tautz, Monika (Islamunterricht im Diskurs. Religionspädagogische und fachdidaktische Ansätze)

Radiocarbon Dating Of Manuscripts Kept in the Central Library of the University of Tehran - Aghaei Abrandabadi, Seyed Ali; Bahrololoumi, Faranak; Hajdas, Irka; Jafarian, Rasul; Kordavani, Lili; Marx, Michael

The Hermeneutics of al-Sharīf al-Murtaḍā (d. 436/1044) in the interpretation of Akhbār al-Āḥād in his Kitāb al-Amālī - Aghaei Abrandabadi, Seyed Ali (Hadith Commentary: Continuity and Change)

The Black Humanist Tradition in Anti-Racist Literature: A Fragile Hope - Hartmann, Alexandra

Wie digitale Medien die kommunikative Aushandlung von Freundschaften verändern - Teichert, Jeannine

Two Sparsification Strategies for Accelerating Demand-Driven Pointer Analysis - Karakaya, Kadiray; Bodden, Eric (2023 IEEE Conference on Software Testing, Verification and Validation (ICST))

Privacy-Preserving Collection and Evaluation of Log Files - Koch, Angelina

Förderung von digitalisierungsbezogenen Kompetenzen von angehenden Physiklehrkräften mit dem SQD-Modell im Projekt DiKoLeP - Weiler, David; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Lachner, Andreas; Riese, Josef; Schubatzky, Thomas (Lehr-Lern-Labore und Digitalisierung)

The Impact of the German Fuel Discount on Prices at the Petrol Pump - Seiler, Volker; Stöckmann, Nico (German Economic Review)
Abstract This paper investigates the price impact of the fuel discount in Germany, which was introduced between June and August 2022 to partially compensate increased energy costs. Using the augmented synthetic control method (ASCM) to construct the counterfactual, we provide quantitative evidence to the heated debate concerning the impact of this policy tool and find the fuel discount to have decreased consumer prices of petrol (diesel) by at least 0.30 euro per litre (0.10 euro per litre) on average. The results are robust to various sensitivity checks. Thus, oil companies and petrol stations decreased prices for consumers and passed on about 85 % (65 %) of the discount in case of petrol (diesel). Moreover, we do not find signs of excessive price increases in anticipation of the fuel discount.
Keywords: Economics and Econometrics

Glaubende Grundhaltung als Zugang zum IslamTheologische Kompetenzen von islamischen Religionslehrkräften - Kamcili-Yildiz, Naciye (Islamischer Religionsunterricht in Deutschland)

Powder Production via Atomisation and Subsequent Laser Powder Bed Fusion Processing of Fe+316L Steel Hybrid Alloy - Pramanik, Sudipta; Andreiev, Anatolii; Hoyer, Kay-Peter; Krüger, Jan Tobias; Hengsbach, Florian; Kircheis, Alexander; Zhao, Weiyu; Fischer-Bühner, Jörg; Schaper, Mirko (Powders)
The current investigation shows the feasibility of 316L steel powder production via three different argon gas atomisation routes (closed coupled atomisation, free fall atomisation with and without hot gas), along with subsequent sample production by laser powder bed fusion (PBF-LB). Here, a mixture of pure Fe and atomised 316L steel powder is used for PBF-LB to induce a chemical composition gradient in the microstructure. Optical microscopy and μ-CT investigations proved that the samples processed by PBF-LB exhibit very little porosity. Combined EBSD-EDS measurements show the chemical composition gradient leading to the formation of a local fcc-structure. Upon heat treatment (1100 °C, 14 h), the chemical composition is homogeneous throughout the microstructure. A moderate decrease (1060 to 985 MPa) in the sample’s ultimate tensile strength (UTS) is observed after heat treatment. However, the total elongation of the as-built and heat-treated samples remains the same (≈22%). Similarly, a slight decrease in the hardness from 341 to 307 HV1 is observed upon heat treatment.

3D-structure of intermetallic interface layer in Al–steel clad material - Šlapáková, Michaela; Kihoulou, Barbora; Veselý, Jozef; Minárik, Peter; Fekete, Klaudia; Knapek, Michal; Králík, Rostislav; Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko (Vacuum)
This paper reveals the 3D character of the intermetallic layer at the aluminum–steel interface which pops up above the original sample surface during annealing. Popping out of the intermetallics was proven using atomic force microscopy. The phase expands out of the plane due to the exothermic formation of the Al5Fe2 phase and the feasibility of surface diffusion. Milling by a focused ion beam enabled the comparison of the chemical composition of the surface layer with the bulk interface, showing no difference. The growth direction is both towards aluminum and steel — the main diffusion flux is from aluminum towards steel, and the new intermetallic phase emerges at the steel side. The shortage of Al atoms causes a shift of the intermetallic as a whole towards aluminum.
Keywords: Al-steel clad; twin-roll casting; 3D characterization; atomic force microscopy; diffusion direction; surface growth

Powder bed fusion of soft-magnetic iron-based alloys with high silicon content - Andreiev, Anatolii; Hoyer, Kay-Peter; Hengsbach, Florian; Haase, Michael; Tasche, Lennart; Duschik, Kristina; Schaper, Mirko (Journal of Materials Processing Technology)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Computer Science Applications; Modeling and Simulation; Ceramics and Composites

Crowdwork in the Age of Algorithms – How Algorithmic Requesters affect the Meaningfulness of Crowdwork - Laux, Florian; Haff, André; Kundisch, Dennis

Heinrich A. Meyer-Reichenau: "Der kecke Griff nach der Bibel und die davongetragene Beute". Studien zur Predigt und Theologie des Bremer Pfarrers Gottfried Menken (1768-1831) - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Katharina Herrmann: Gesungene Katechese. Kommunikation durch Popularisierung. Kulturelle Repräsentation eines engagierten protestantischen Christentums im Neuen Geistlichen Lied - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Thorsten Knauth/Rainer Möller/Annebelle Pithan (Hg.), Inklusive Religionspädagogik der Vielfalt. Konzeptionelle Grundlagen und didaktische Konkretionen. Münster/New York 2020 - Schroeter-Wittke, Harald (Zeitschrift für Pädagogik und Theologie)